Catch and release: Testing the effect of a citation release policy on crime in Washington, DC - Riddell, Jordan R. (Criminology & public policy, 2024)
Research summary This study investigated the effect of an expanded police station citation release policy enacted in Washington, DC in March 2020 on eight types of crime: homicide, sex abuse, robbery, assault with a dangerous weapon, burglary, motor vehicle theft, theft from motor vehicles, and other theft. Monthly-level multivariate time series analyses employed data from 2013-2022 and accounted for the relationship between crime, arrests, and the jail population. The expanded policy was hypothesized to increase certain property crimes based on the new guidelines, but results indicated the policy modification was associated with changes in citywide crime counts for one type of crime: homicide. Policy implications Efforts around the United States to decarcerate the pre-trial jail population should examine potential unintended consequences for public safety. The current study failed to detect a statistically significant increase in seven of the eight types of crime during the expanded use of one jail decarceration approach, police station citation release. In the future, jurisdictions looking to reduce their jail population might consider citation release as a speedy and cost-effective alternative to release-on-recognizance, but they should take care to monitor individual defendants and evaluate their own program.